Molybdenum diselenide thin films grown by atomic layer deposition: An XPS analysis - Rodriguez Pereira, Jhonatan; Zazpe, Raul; Charvot, Jaroslav; Bureš, Filip; Macák, Jan (American Institute of Physics, 2020)
Molybdenum diselenide (MoSe2) thin films were deposited on annealed titanium foils by atomic layer deposition using suitable precursors. In this paper, a detailed x-ray photoelectron spectroscopy analysis of the MoSe2 film is presented. Survey spectra, Mo 3d, Se 3d, Mo 3p, Se LMM, Se 3p, C 1s, and Se 4s core level along with the valence band spectra were measured. Quantitative analysis indicates a surface composition of MoSe1.8, suggesting a deficiency of selenium on the surface.
Tenké vrstvy MoSe2 připravené depozicí atomárních vrstev: XPS analýzy
Keywords: MoSe2; transition metal dichalcogenides; thin films; 2D material; XPS; MoSe2; dichalkogenidy přechodných prvků; tenké vrstvy; 2D materiály; XPS